Penarikan: Formulasi Ekstrak Siwak (Salvadora persica) Sebagai Mouth Spray dan Uji Efektivitas Terhadap Bakteri Staphylococcus aureus - Nugraha, Nasywa Fatihah Bintang; Fauzi, Ahmad; Dwi Astuti, Elsa (Fakultas Farmasi Universitas Tjut Nyak Dhien, 2025)
Retraction: Mouth-related problems often occur in human life, one of which is bad breath. Mouth spray is a health product that contains a combination of active ingredients and additional ingredients such as antibacterial, freshener, or moisturizer that work to support dental and oral health. Miswak (Salvadora persica) contains large amounts of chloride, fluorine, trimethylamine and resin, silica sulfur and vitamin C, where these chemical ingredients have great benefits for dental and oral health. This study aims to formulate miswak extract in the form of a mouth spray preparation and test its effectiveness against Staphylococcus aureus bacteria and use Simple Lattice Design as an optimization method. Extraction was carried out by the maceration method using 96% ethanol, then the extract was formulated in the form of a mouth spray preparation. The physical properties of the mouth spray were evaluated through organoleptic tests, pH, clarity and viscosity, while the antibacterial activity test was carried out by the well diffusion method. The results of the organoleptic test showed that all formulas had a dark brown color and a distinctive odor. The results of the clarity test for the five formulas looked clear and there were no visible particles. The pH test showed that all formulas had pH results within the safe range. The viscosity test did not meet the requirements, with an average result of 11.43 ± 0.52 cP. The antibacterial test showed that the miswak extract had antibacterial activity with an inhibition zone diameter of 16.25 mm against Staphylococcus aureus bacteria.